Thermal Energy Storage Using Phase Change Materials Fundamentals and Applications - Fleischer, Amy S. (SpringerBriefs in Thermal Engineering and Applied Science, 2015)
This book presents a comprehensive introduction to the use of solid‐liquid phase change materials to store significant amounts of energy in the latent heat of fusion. The proper selection of materials for different applications is covered in detail, as is the use of high conductivity additives to enhance thermal diffusivity. Dr. Fleischer explores how applications of PCMS have expanded over the past 10 years to include the development of high efficiency building materials to reduce heating and cooling needs, smart material design for clothing, portable electronic systems thermal management, solar thermal power plant design and many others. Additional future research directions and challenges are also discussed.